Numerical modeling of two-dimensional heat-transfer and temperature-based calibration using simulated annealing optimization method: Application to gas metal arc welding - Bjelić Mišo B. (Thermal Science, 2016)
Simulation models of welding processes allow us to predict influence of welding parameters on the temperature field during welding and by means of temperature field and the influence to the weld geometry and microstructure. This article presents a numerical, finite-difference based model of heat transfer during welding of thin sheets. Unfortunately, accuracy of the model depends on many parameters, which cannot be accurately prescribed. In order to solve this problem, we have used simulated annealing optimization method in combination with presented numerical model. This way, we were able to determine uncertain values of heat source parameters, arc efficiency, emissivity and enhanced conductivity. The calibration procedure was made using thermocouple measurements of temperatures during welding for P355GH steel. The obtained results were used as input for simulation run. The results of simulation showed that represented calibration procedure could significantly improve reliability of heat transfer model. [National CEEPUS Office of Czech Republic (project CIII-HR-0108-07-1314) and to the Ministry of Education and Science of the Republic of Serbia (project TR37020)]